2017
DOI: 10.3390/nu9070718
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role for Antioxidants in Acute Kidney Disease

Abstract: Acute kidney injury causes significant morbidity and mortality in the community and clinic. Various pathologies, including renal and cardiovascular disease, traumatic injury/rhabdomyolysis, sepsis, and nephrotoxicity, that cause acute kidney injury (AKI), induce general or regional decreases in renal blood flow. The ensuing renal hypoxia and ischemia promotes the formation of reactive oxygen species (ROS) such as superoxide radical anions, peroxides, and hydroxyl radicals, that can oxidatively damage biomolecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(120 citation statements)
references
References 152 publications
(258 reference statements)
4
93
0
2
Order By: Relevance
“…La vitamina C tiene efectos inmunoestimulantes, propiedades antioxidantes, antiinflamatorias, antivirales y posibles efectos antimutagénicos 3,4 . Se ha demostrado que la vitamina C mejora la quimiotaxis de neutrófilos, la fagocitosis y, por lo tanto, el aclaramiento microbiano 5,6 . Además, promueve la proliferación de células T y células natural killer que modulan sus funciones 7 .…”
Section: Efectos Biológicosunclassified
“…La vitamina C tiene efectos inmunoestimulantes, propiedades antioxidantes, antiinflamatorias, antivirales y posibles efectos antimutagénicos 3,4 . Se ha demostrado que la vitamina C mejora la quimiotaxis de neutrófilos, la fagocitosis y, por lo tanto, el aclaramiento microbiano 5,6 . Además, promueve la proliferación de células T y células natural killer que modulan sus funciones 7 .…”
Section: Efectos Biológicosunclassified
“…Among vitamin C’s pleiotropic functions that are of relevance to critical illness are its immune-enhancing effects, anti-oxidant properties, and potential anti-mutagenic effects[ 11 , 12 ]. Vitamin C has been shown to enhance neutrophil chemotaxis, phagocytosis, and thus microbial clearance[ 13 , 14 ].…”
Section: Biological Effects Of Vitamin Cmentioning
confidence: 99%
“…Endothelial cell Capn4 deficiency reduced renal NO and ROS production in endotoxemic mice by inhibiting iNOS expression NO and ROS are involved in the pathological process of renal injury 23 . Our previous research showed that inhibiting calpain by overexpressing calpastatin decreased NO production in a model of diabetes 11 .…”
Section: Calpain Activation Was Involved In Lps-induced Pmec Apoptosismentioning
confidence: 97%